2011
DOI: 10.1055/s-0031-1292053
|View full text |Cite
|
Sign up to set email alerts
|

Vaskuläres Altern, Hypertonie und körperliche Aktivität

Abstract: The present review delineates the significance of intima-media-thickness, arterial stiffness and endothelial function for vascular aging. There is profound evidence for an increase in intima-media-thickness and vascular stiffness not only during healthy aging but induced also by cardiovascular risk factors. There is a central role of arterial hypertension for this progression in both structural factors. In addition, both parameters are strongly associated with cardiovascular risk. Endothelial function measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Кроме того, увеличение физической активности было связано с более низким 5-летним прогрессированием СРПВ (на 0,16 м/с). По результатам исследования более активный образ жизни вели пациенты с супернормальным сосудистым старением, в то время как участники с преждевременным сосудистым старением более длительное время проводили в положении сидя, что согласуется с имеющимися данными о благоприятном влиянии физических упражнений на сосудистую стенку [29]. По результатам другого исследования авторы также продемонстрировали, что регулярные аэробные упражнения умеренной интенсивности, которые могут быть доступны большинству пациентов, способны снижать артериальную жесткость [30].…”
Section: материал и методыunclassified
“…Кроме того, увеличение физической активности было связано с более низким 5-летним прогрессированием СРПВ (на 0,16 м/с). По результатам исследования более активный образ жизни вели пациенты с супернормальным сосудистым старением, в то время как участники с преждевременным сосудистым старением более длительное время проводили в положении сидя, что согласуется с имеющимися данными о благоприятном влиянии физических упражнений на сосудистую стенку [29]. По результатам другого исследования авторы также продемонстрировали, что регулярные аэробные упражнения умеренной интенсивности, которые могут быть доступны большинству пациентов, способны снижать артериальную жесткость [30].…”
Section: материал и методыunclassified
“… 20 Regular aerobic physical activity of moderate intensity has been shown in adults to be associated with lower arterial stiffness and lower carotid intima-media thickness (IMT). 21 22 In contrast, in sedentary healthy adults, ageing is associated with increased stiffness of the large elastic arteries and with poorer vascular endothelial function and increased mortality. 22 23 The EVIDENT study found an association of physical activity with better vascular structure and function and sedentary time (hours spent watching television) with greater arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%